Metabolic Changes Induced by Purinergic Signaling: Role in Food Intake - Caruso, Vanni; Zuccarini, Mariachiara; Di Iorio, Patrizia; Muhammad, Ishaq; Ronci, Maurizio (Frontiers in Pharmacology, 2021)
The purinergic signalling has a well-established role in the regulation of energy homeostasis, but there is growing evidence of its implication in the control of food intake. In this review, we provide an integrative view of the molecular mechanisms leading to changes in feeding behaviour within hypothalamic neurons following purinergic receptor activation. We also highlight the importance of purinergic signalling in metabolic homeostasis and the possibility of targeting its receptors for therapeutic purposes.